2014
DOI: 10.1101/gad.236547.113
|View full text |Cite
|
Sign up to set email alerts
|

Conserved residues in yeast initiator tRNA calibrate initiation accuracy by regulating preinitiation complex stability at the start codon

Abstract: Eukaryotic initiator tRNA (tRNA i ) contains several highly conserved unique sequence features, but their importance in accurate start codon selection was unknown. Here we show that conserved bases throughout tRNA i , from the anticodon stem to acceptor stem, play key roles in ensuring the fidelity of start codon recognition in yeast cells. (PICs). Disrupting the C3:G70 base pair in the acceptor stem produces a Sui -phenotype and also reduces the rate of TC binding to 40S subunits in vitro and in vivo. Both d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
29
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 27 publications
(34 citation statements)
references
References 55 publications
5
29
0
Order By: Relevance
“…Met were chased with excess unlabeled TC, incubated for increasing time periods, and then resolved via native gel electrophoresis to separate 40S-bound and unbound fractions of TC. In agreement with previous findings (11,29,30), little to no TC dissociation occurred from WT PICs formed with the AUG-containing mRNA [mRNA(AUG)] over the time course Fig. 2A with the indicated RPS3 alleles were cultured in SD+His+Trp+Ura medium to an A 600 of ∼1.0 and WCEs were subjected to Western analysis using antibodies against eIF1 or Hcr1 (as loading control).…”
Section: Rps3supporting
confidence: 90%
See 1 more Smart Citation
“…Met were chased with excess unlabeled TC, incubated for increasing time periods, and then resolved via native gel electrophoresis to separate 40S-bound and unbound fractions of TC. In agreement with previous findings (11,29,30), little to no TC dissociation occurred from WT PICs formed with the AUG-containing mRNA [mRNA(AUG)] over the time course Fig. 2A with the indicated RPS3 alleles were cultured in SD+His+Trp+Ura medium to an A 600 of ∼1.0 and WCEs were subjected to Western analysis using antibodies against eIF1 or Hcr1 (as loading control).…”
Section: Rps3supporting
confidence: 90%
“…A smaller fraction of complexes formed with mRNA (UUG) accesses this highly stable state, and the remainder dissociates with a measurable off-rate. Thus, the extent of dissociation reflects the ratio of PICs in P IN versus the distinct, hyperstable conformation, and the rate of dissociation reflects the stability of the P IN conformation (11,30). Accordingly, the results in Fig.…”
Section: Rps3mentioning
confidence: 88%
“…8A). In yeast, the 3GC tRNAs also showed stable binding to the 40S (28,29) but not the 80S ribosomes (28), supporting our proposal of the role of the 3GC pairs, a feature of initiator tRNAs conserved in all domains of life. In vitro studies using 70S ribosomes also showed that the 3GC pairs are required for tRNA fMet binding to the ribosome (4).…”
Section: Discussionsupporting
confidence: 69%
“…4G). Previous work indicated that TC bound in the P OUT conformation is too unstable to remain associated with the PIC during native gel electrophoresis, such that the measured rate of TC dissociation in these assays largely reflects the proportion of complexes in the P IN state and the stability of that state (22,23). In agreement with previous findings (22), we observed that TC dissociates more rapidly from the mRNA(UUG) versus mRNA(AUG) PICs in reactions containing WT eIF1 ( Fig.…”
Section: Substitutions Of Eif1 Loop 2 Residues Decrease Discriminationmentioning
confidence: 99%